Radiation exposure of patients during endourological procedures: IAEA-SEGUR study. (20th November 2020) - Vassileva, Jenia; Zagorska, Anna; Basic, Dragoslav; Karagiannis, Andreas; Petkova, Kremena; Sabuncu, Kubilay; Saltirov, Iliya; Sarica, Kemal; Skolarikos, Andreas; Stavridis, Sotir; Trinchieri, Alberto; Tzelves, Lazaros; et al.
Abstract: Fluoroscopy is increasingly used to guide minimally invasive endourological procedures and optimised protocols are needed to minimise radiation exposure while achieving best treatment results. This multi-center study of radiation exposure of patients was conducted by the South-Eastern European Group for Urolithiasis Research (SEGUR), in cooperation with the International Atomic Energy Agency. Seven clinical centers from the SEGUR group collected data for 325 procedures performed within a three-months period, including standard percutaneous nephrolithotomy (PCNL), mini PCNL, retrograde intrarenal surgery (RIRS), semirigid ureterorenoscopy (URS) and flexible URS. Data included: air kerma area product ( P KA ), air kerma at the patient entrance reference point ( K a, r ), fluoroscopy time (FT), number of radiographic images ( N ) and fluoroscopy pulse rate, as well as total procedure duration, size and location of stones. Data were centrally analysed and statistically compared. Median P KA values per center varied 2-fold for RIRS (0.80–1.79 Gy cm 2 ), 7.1 fold for mini-PCNL (1.39–9.90 Gy cm 2 ), 7.3 fold for PCNL (2.40–17.50 Gy cm 2 ), 19 fold (0.13–2.51 Gy cm 2 ) for semi-rigid URS and 29-fold for flexible URS (0.10–2.90 Gy cm 2 ). Lower P KA and K a, r were associated with use of lower FT, N and lower fluoroscopy pulse rate. FT varied from 0.1 to 14 min, a small fraction of the total procedure time, ranging from 10 to 225 min. Higher N was associated with higher P KA and K a, r . Higher median P KA in PCNL was associated with the use of supine compared to prone position. No correlation was found between the concrement size and procedure duration, FT, P KA or K a, r . Dose values for RIRS were significantly lower compared to PCNL. The maximum K a, r value of 377 mGy was under the threshold for radiation induced skin erythema. The study demonstrated a potential for patient dose reduction by lowering FT and N, using pulsed fluoroscopy and beam collimation.